Structure development of the HP3 instrument Support System for the Mars mission InSight. (November 2019) - Reershemius, Siebo; Fittock, Mark; Hudson, Troy L.; Sasaki, Kaname; Scharringhausen, Marco; Spohn, Tilman; Spröwitz, Tom; Wippermann, Torben
Abstract: On May 05, 2018 NASA JPL launched its mission to Mars called "InSight". Main objective of this mission is to gain more knowledge of the evolution of terrestrial planets. Beside a number of different scientific instruments onboard the lander there are two instruments that will perform measurements on the Martian ground. One of the instruments is HP 3 (Heat Flow and Physical Properties Package), which was developed by the German Aerospace Center (DLR) to measure the heat flow of the Martian outer crust. Main elements of this instrument are the heat flow probe, the Backend Electronic and the Support System. With this paper the authors give a detailed insight of the function of the Support System within the instrument and its development. The Support System enables the operation of the heat flow probe on the surface. The mechanical design of the Support System is mainly driven by a unique set of requirements derived from the working environment on Mars, the deployment from the lander deck, and the mechanically separated operation on the surface. The paper will give an overview of the development and the qualification of the structure of the Support System. It will focus on the mechanical design and the analysis of the structural dynamics, and on the testing which includes standard environmental testing but also numerous development tests that are very mission specific.